2013
DOI: 10.1074/jbc.m113.494328
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead Box O1 (FOXO1) Protein, but Not p53, Contributes to Robust Induction of p21 Expression in Fasted Mice

Abstract: Background: p21 is a cell cycle regulator with no known role in metabolic regulation. Results: Fasting induces a potent p53-independent increase in p21 expression in metabolic tissues and Forkhead Box O1 (FOXO1) contributes to this response in liver. Conclusion: This study advances the role of p21 in metabolic stress response. Significance: Metabolic stress induces a cell cycle regulator even in non-dividing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…Loss of SATB1 in DA neurons caused a ~300% elevation in CDKN1A transcription, but did not significantly alter levels in CTX neurons. It is tempting to speculate that the CDKN1A locus is under a constant transcriptional activation pressure in DA neurons compared to CTX neurons, which is reflected by significantly higher expression of CDKN1A-promoting factors ( Figure S5 D,E; Tinkum et al, 2013). These findings suggest that the intrinsic properties of DA neurons, be they structural (size, branching), energetic demand, or high stress level (Pacelli et al, 2015) may render these cells vulnerable to cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of SATB1 in DA neurons caused a ~300% elevation in CDKN1A transcription, but did not significantly alter levels in CTX neurons. It is tempting to speculate that the CDKN1A locus is under a constant transcriptional activation pressure in DA neurons compared to CTX neurons, which is reflected by significantly higher expression of CDKN1A-promoting factors ( Figure S5 D,E; Tinkum et al, 2013). These findings suggest that the intrinsic properties of DA neurons, be they structural (size, branching), energetic demand, or high stress level (Pacelli et al, 2015) may render these cells vulnerable to cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…This research was originally published in ref. 61. Copyright (2013) the American Society for Biochemistry and Molecular Biology.…”
Section: Figmentioning
confidence: 99%
“…[138,148] Osmotic pumps and alternative delivery mechanisms will also be useful in this regard. [61,147]…”
Section: Introductionmentioning
confidence: 99%
“…In a 2010 study of C57Bl/6 mice undergoing a 48-h food deprivation, p21/Cdkn1a expression was significantly up-regulated (Poplawski et al 2010). More recently, in a 2013 paper, liver and hypothalamus of mice fasted 24 and 48 h showed significant induction of a p21/Cdkn1a promoter construct (Tinkum et al 2013). Further examination of our dataset revealed that there were many genes with GO categories related to cell cycle processes.…”
Section: Discussionmentioning
confidence: 69%